Development of Herbal Booster Product “A5I (Katuk (S. androgynus (L.) Merr.), Moringa (M. oleifera), Fenugreek (T. foenum-graecum L.), Torch Ginger (Etlingera elatior), Cinnamon (Cinnamomum burmannii))” as a Lactagogue Based on Clinical Observational Study - Eva Kusumahati; Kintoro Kintoro; Sagiran Sagiran (Universitas Islam Negeri Ar-Raniry, 2026)
Inadequate exclusive A5I provision is a risk factor for stunting, which remains a major health problem in Indonesia. A polyherbal tea product A5I containing katuk (Sauropus androgynus), moringa (Moringa oleifera), klabet (Trigonella foenum-graecum), torch ginger (Etlingera elatior), and cinnamon (Cinnamomum burmannii) was developed as a natural lactagogum. This study aimed to evaluate the safety of the product through histopathological analysis of vital organs and mammary tissue in female mice after repeated administration. A 28-day subchronic toxicity test was conducted on female mice divided into control and treatment groups. The heart, lungs, kidneys, and mammary organs were harvested for histopathological examination using hematoxylin-eosin staining with a standardized scoring system. Myocardial histopathology showed minimal bleeding without necrosis. The lungs exhibited alveolar septal destruction and mild inflammatory cell infiltration without pulmonary edema, indicating a functional alveocapillary barrier. The kidneys exhibited only mild tubular degeneration without necrosis or inflammatory infiltration. Mammary tissue exhibited extensive ductal dilation and abundant intraluminal secretion distribution, consistent with active lactation. Subchronic administration of A5I polyherbal tea did not cause significant histopathological damage to vital organs, and the mammary findings support its potential lactagogic effect. These findings provide preliminary evidence of the safety of this polyherbal product as a breast milk booster, although further studies with larger sample sizes are needed to confirm its safety and clinical effectiveness. Keyword: Breastfeeding Booster; Histopathology; Lactagogue; Mammary Gland; Mice; Polyherbal